The comparison of physic-chemical properties of chitosan/collagen/hyaluronic acid composites with nano-hydroxyapatite cross-linked by dialdehyde starch and tannic acid. (September 2017) - Kaczmarek, B.; Sionkowska, A.; Osyczka, A.M.
Abstract: Scaffolds based on chitosan, collagen and hyaluronic acid, cross-linked by dialdehyde starch with hydroxyapatite were obtained with the use of the freeze-drying method. Scaffolds were cross-linked by tannic acid or dialdehyde starch addition. Composites were characterized by different analyses, e.g. SEM images, porosity, density, liquid uptake, and mechanical tests. In addition, the adhesion and proliferation of human osteosarcoma SaOS-2 cells were examined on the obtained scaffolds. The results showed that the properties of the scaffolds based on chitosan, collagen, and hyaluronic acid can be modified by cross-linkers addition. The compressive modulus for the scaffolds cross-linked by dialdehyde starch was higher than for those cross-linked by tannic acid. The porosity of scaffolds cross-linked by starch was higher than those in which tannic acid was applied. However, the former presented lower density. SEM images showed the homogeneous scaffold structure with interconnected pores. Scaffolds cross-linked by tannic acid exhibited higher biocompatibility than those cross-linked by dialdehyde starch. However, the results showed that both scaffolds, cross-linked by dialdehyde starch and by tannic acid can provide the support required in tissue engineering and regenerative medicine. The scaffolds presented here may be easily operated to fit such small bone defects without causing adverse reactions.